Hepatic adaptations to maintain metabolic homeostasis in response to fasting and refeeding in mice. Issue 1 (December 2016) - Geisler, C.; Hepler, C.; Higgins, M.; Renquist, B.
Abstract Background The increased incidence of obesity and associated metabolic diseases has driven research focused on genetically or pharmacologically alleviating metabolic dysfunction. These studies employ a range of fasting-refeeding models including 4–24 h fasts, "overnight" fasts, or meal feeding. Still, we lack literature that describes the physiologically relevant adaptations that accompany changes in the duration of fasting and re-feeding. Since the liver is central to whole body metabolic homeostasis, we investigated the timing of the fast-induced shift toward glycogenolysis, gluconeogenesis, and ketogenesis and the meal-induced switch toward glycogenesis and away from ketogenesis. Methods Twelve to fourteen week old male C57BL/6J mice were fasted for 0, 4, 8, 12, or 16 h and sacrificed 4 h after lights on. In a second study, designed to understand the response to a meal, we gave fasted mice access to feed for 1 or 2 h before sacrifice. We analyzed the data using mixed model analysis of variance. Results Fasting initiated robust metabolic shifts, evidenced by changes in serum glucose, non-esterified fatty acids (NEFAs), triacylglycerol, and β-OH butyrate, as well as, liver triacylglycerol, non-esterified fatty acid, and glycogen content. Glycogenolysis is the primary source to maintain serum glucose during the first 8 h of fasting, while de novo gluconeogenesis is the primary source thereafter. The increase in serum β-OH butyrate results from increased enzymatic capacity for fatty acid flux through β-oxidation and shunting of acetyl-CoA toward ketone body synthesis (increased CPT1 (Carnitine Palmitoyltransferase 1) and HMGCS2 (3-Hydroxy-3-Methylglutaryl-CoA Synthase 2) expression, respectively). In opposition to the relatively slow metabolic adaptation to fasting, feeding of a meal results in rapid metabolic changes including full depression of serum β-OH butyrate and NEFAs within an hour. Conclusions Herein, we provide a detailed description of timing of the metabolic adaptations in response to fasting and re-feeding to inform study design in experiments of metabolic homeostasis. Since fasting and obesity are both characterized by elevated adipose tissue lipolysis, hepatic lipid accumulation, ketogenesis, and gluconeogenesis, understanding the drivers behind the metabolic shift from the fasted to the fed state may provide targets to limit aberrant gluconeogenesis and ketogenesis in obesity.